Association of the serological status of rheumatoid arthritis patients with two circulating protein biomarkers: A useful tool for precision medicine strategies - Ruiz-Romero, Cristina; Fernández-Puente, Patricia; González, Lucía; Illiano, Anna; Lourido, Lucía; Paz, Rocío; Quaranta, Patricia; Perez-Pampín, Eva; González, Antonio; Blanco, Francisco J.; Calamia, Valentina (Frontiers in Medicine, 2022)
Rheumatoid Arthritis (RA) is an autoimmune disease characterized by inflammation of the joints and presence of autoantibodies. The heterogeneity of RA patients has hampered its management. Rheumatoid Factor (RF) and anti-citrullinated protein antibodies (ACPA) are key for the diagnosis of RA, however, additional serological markers will improve the clinical management of this disease, enabling further patient stratification and application of precision medicine strategies. In this work, we investigated serum proteins associated with RF and/or ACPA in RA patients. An iTRAQ-based shotgun proteomic analysis was performed on sera from the RA cohort of the Hospital of Santiago de Compostela (CHUS). A Multiple Reaction Monitoring (MRM) method was developed using Skyline and the targeted analysis was performed using peptides with internal labelled standards. Serum levels of orosomucoid 1 (A1AG1), haptoglobin (HPT) and retinol-binding protein 4 (RET4) were measured by immunoassays in the RA cohort of the Hospital of A Coruña (HUAC). For the discovery phase, sera samples from the CHUS cohort were pooled according to their RF/ACPA status. LC-MS/MS analysis showed that the abundance of 12 proteins was altered in RF+/ACPA+, 16 in RF+/ACPA- and 10 in RF-/ACPA+, all compared to RF-/ACPA-. Vitamin D binding protein and haptoglobin were the unique proteins increased in all the comparisons. For verification, 80 samples from the same cohort were analyzed individually. Then, 31 peptides belonging to 12 proteins associated with RF and/or ACPA status were quantified by MRM. Three acute phase reactants (A1AG1, AACT and HPT) were verified in this phase. The increase of two of these putative biomarkers in the double seropositive group was then validated in 260 patients from CHUAC cohort (p=0,009 A1AG1; p=0,003 HPT). Finally, the increased level of A1AG1 showed association with RF rather than ACPA (p=0,023), whereas HPT with ACPA rather than RF (p=0,013). The determination of A1AG1 and HPT in sera provides novel information useful for patient stratification, which might facilitate the development of personalized medicine in RA.